INISIASI PEMBERDAYAAN EKONOMI KREATIF BERBASIS DAUR ULANG PLASTIK DI DESA CIJAMBU - Januarsyah, Gilang; Rahayu, Lina Meilinawati; Priyatna, Aquarini; Prabasmoro, Tisna; Adji, Muhamad; Purwaramdhona, Ananda Bintang (Midang, 2026)
Household plastic waste remains an environmental challenge in many rural areas, including Cijambu Village, Tanjungsari District, Sumedang Regency. Used plastic bags, commonly regarded as waste, have the potential to be transformed into creative products with functional and economic value. This article aims to describe the initiation of a creative economy empowerment program based on plastic recycling through collaboration among the community service team of Faculty of Cultural Sciences Universitas Padjadjaran, village authorities, and BIYA Project as a creative industry partner. The method employed was a participatory approach consisting of coordination, preliminary observation, partnership development, and preparation for training activities involving women’s community groups in Cijambu Village. The program engaged Keni Kurniasari Soeriaatmadja from BIYA Project as a plastic recycling practitioner who provided assistance in developing creative products made from used plastic materials. The initial results indicate strong support from the village government, reflected in the issuance of activity permits and the involvement of village officials in the preparation process. In addition, a training program on transforming used plastic bags into practical products has been scheduled for July 2026. This article highlighted the collaboration between universities and village governments, and BIYA Project represents an important initial step in developing a community empowerment model based on circular economy principles and sustainable waste management.